Some Problems in the Use of the Medical Nomenclature and Terminology in Indonesia: A Preliminary Study - Ahmad W Pratiknya, Ahmad W Pratiknya (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
Although medical science and practice have developed for a long time in Indonesia, there are still many difficulties and confusions in the use of the medical nomenclature and terminology. This fact is due to the imbalance between the fast rate of transfer of science and the slow rate of language transfer, especially in the field of medicine.The main problems identified are:a. Which procedure should be chosen in the language transfer and what should be done with the declination rule?b. How should the transfer be carried out in different fields of medical terminology? To anticipate these problems, five alternatives of language transfer are forwarded, i., e.:1. full adaptation,2. adaptation without declination,3. translation,4. full transcription, and5. transcription without declination.The last alternative is recommended to be used in IT/05t fields of medical terminology.Key Words: medical nomenclature - terminology - language transfer - translation - transcription